An overview of Teletandem mediation courses for teacher education - Souza, Micheli Gomes de; Zakir, Maisa de Alcantara; Garcia, Daniela Nogueira de Moraes (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2022)
This paper aims to investigate practices in teacher education in the context of the Teletandem Brasil Project (Vassallo & Telles, 2006). Through web conferencing tools, the project pairs up Brazilian university students learning foreign languages with foreign university students learning Portuguese. The partnerships are supported by mediation sessions conducted by professors and researchers of the Teletandem Project. In this paper, we present some theoretical concepts related to telecollaboration (Belz, 2003; O’Dowd, 2007; 2018), besides providing a detailed description and comparison of four editions of preparatory courses for teletandem mediators, organized by researchers of the project. The results of the analysis may provide alternatives for teacher education in a context of growing transcultural connections.